Analisis Kinerja Ruas Jalan Sam Ratulangi Depan Kampus Universitas Flores Akibat Parkir di Badan Jalan - Ireneus Kota; Mansuetus Gare; Ferdinandus Mesi Muda; Veronika Miana Radja (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2022)
On Street Parking is parking that is carried out on the body of the road by using part of the road. The function of the road to channel traffic flow will be reduced in capacity because part of the road is used for parking facilities. This condition can become a problem if the traffic growth continues, both by population growth and the number of vehicles. This study aims to determine the effect of On Street Parking activities on the performance of Jalan Sam Ratulangi in front of the Flores University Campus. The data collected includes data on traffic volume, road geometry, side barriers, speed, and On Street Parking data. The method used in the traffic volume survey is manual observation or traffic counting which is carried out for 12 hours. The data obtained were analyzed using the guidelines for the Indonesian Road Capacity Manual (MKJI 1997). The problem of On Street Parking is enough to affect the performance of roads in general. This is clearly seen at the observation location of the Sam Ratulangi road in front of the University of Flores campus where the volume at peak hours on Mondays at 11:00–12:00 is 275.00 pcu/hour. The capacity of the road segment is 823.61 pcu/hour with a free flow speed of 25.90 km/hour. The degree of saturation reached 0.204. Meanwhile, for the assumed condition without OSP, the volume at peak hour is 187.00 pcu/hour. The capacity of the road segment increased by 1157.67 pcu/hour to 1344.672 pcu/hour, the free flow speed increased to 28.19 km/hour. The degree of saturation becomes 0.204. The service level of the Sam Ratulangi road for conditions with OSP on or without OSP is at level B where the flow is stable and the speed is slightly controlled and limited by traffic. So it can be concluded that the presence of on street parking in front of the Flores University campus has not shown a significant effect.